Fractional Calculus Operator and Certain Applications in Geometric Function Theory - Irmak, Hüseyin; Tuneski, Nikola (Sarajevo Journal of Mathematics, 2024)
Using a operator involving fractional calculus introduced by Owa and Srivastava [8], two novel families: $${\mathcal V}_{δ}^{α, β}( u;γ)\;\; and \;\;{\mathcal W}_{δ}^{α, β}(μ;γ)$$ $$(δ eq 0,\; α <1,\;β <1,\;γ <1,\;μ≥ 0,\; u\in (-1,0)\cup(0,1))$$ of functions $f(z)$ which are analytic and univalent in the open unit disk ${\mathcal U}$ are defined. Moreover some consequences of main results are shown. 2000 Mathematics Subject Classification. 30C45, 30A10, 26A33